A bioethics for all seasons. Issue 1 (16th December 2014) - Chan, Sarah
Abstract : The last four decades have seen the emergence and flourishing of the field of bioethics and its incorporation into wide-ranging aspects of society, from the clinic or laboratory through to public policy and the media. Yet considerable debate still exists over what bioethics is and how it should be done. In this paper I consider the question of what makes good bioethics. Drawing on historical and contemporary examples, I suggest that bioethics encompasses multiple modes of responding to moral disagreement, and that an awareness of which mode is operational in a given context is essential to doing good bioethics.